Management of Pipkin Fractures Using a Safe Surgical Hip Dislocation - Rita Henriques; Diogo Ramalho; Joaquim Soares do Brito; Pedro Rocha; André Spranger; Paulo Almeida (Case Reports in Orthopedics)
Introduction. Pipkin fractures are rare events and usually occur as a consequence for high-energy trauma. Surgery to obtain anatomical reduction and fixation is the mainstay treatment for the majority of these injuries; nonetheless, controversy exists regarding the best surgical approach. Description of the Case. We present the case of a 41-year-old male, which sustained a type II Pipkin fracture following a motorcycle accident. In the emergency department, an emergent closed reduction was performed, followed by surgery five days later. Using a surgical hip dislocation, a successful anatomical reduction and fixation was performed. After three years of follow-up, the patient presented with a normal range of motion, absent signs for avascular necrosis or posttraumatic arthritis, but with a grade II heterotopic ossification. Discussion. Safe surgical hip dislocation allows full access to the femoral head and acetabulum, without increasing the risk for a femoral head avascular necrosis or posttraumatic arthritis. Simultaneously, this surgical approach gives the opportunity to repair associated acetabular or labral lesions, which explains the growing popularity with this technique. Conclusion. Although technically demanding, safe surgical hip dislocation represents an excellent option in the reduction and fixation for Pipkin fractures.